Meningkatkan Motivasi, Aktivitas, dan Hasil Belajar IPS Menggunakan Model BATIK pada Siswa Kelas V SDN Manarap Lama 1 - Dewi Nugraheni; Raihanah Sari (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low motivation, activity and student learning outcomes in social studies learning. This study aims to analyze motivation, activity, and improvement of student learning outcomes. This research was carried out using a qualitative and quantitative approach with the type of Classroom Action Research (CAR) which was held in 4 meetings in the VA class of SDN Manarap Lama 1 in the academic year 2022/2023 with a total of 27 students. The research instrument used observation sheets of teacher activity, observation of student activity, student learning motivation questionnaires and student learning outcomes. Then analyzed with descriptive techniques and described in the form of tables and graphs. The results showed that teacher activity increased and reached a percentage of 96.87% with the criteria "Very Good", student motivation increased 96.30% with the criteria "Almost All Students Are Motivated", student activity increased 96.30% with the criteria "Almost All Active Students", and student learning outcomes increased by 90.12% of "Complete" students. Based on the results of the study it was concluded that the BATIK model can significantly increase student motivation, activity and learning outcomes. It is recommended to use this model as material for consideration and alternatives in selecting learning models to improve the quality of learning in schools.